PENGARUHCITRAPERUSAHAANDANKEPUASAN TERHADAPKEPERCAYAAN DANDAMPAKNYAPADALOYALITAS (Studi Pada Klien Asuransi Prudential Pru Vision Kabupaten Pati) - Tjahjaningsih, Endang; Maskur, Ali (Proceeding Fakultas Ekonomi, 2015)
This study aims to determine the influence companyâs image and satisfaction with trust andits impact to clients loyalty on Prudentials insurance Pru Vision Pati. Total sample are 100 respondents, by using purposive sampling method with criteria that clients have become customers of at least 3 years. Analysis of the data in this study using regression analyzing. Hypothesis testing is used t calculated at the level of significance (Î±) 5%. Where mediation test using path analysis. Result of regression analysis in this study resulted in the coefficient of determination for 0,941 or in other words the changes in loyalty can be affected by the companyâs image, satisfaction and trust of 4,1%. The results of this study show that companyâs image positive and significant impact on clients trust, satisfaction positive and significant impact on clients trust, companyâs image positive and significant impact on clients loyalty, satisfaction positive and significant impact on clients loyalty, trust positive and significant impact on clients loyalty, and trust does not mediate the influence of companyâs image and satisfaction of the clients loyalty.Keyword: Companyâs image, Satisfaction, Trust, Loyalty